KONSERVASI SUMBER AIR DAN WISATA EDUKASI DI DESA NGENEP KECAMATAN KARANGPLOSO KABUPATEN MALANG - Prihanta, Wahyu; Purwanti, Ely; Zainuri, Ach. Muhib (Perkumpulan Legowo Cerdas Sejahtera, 2024)
Ngenep Village, Karangploso District, Malang Regency has the potential of natural resources in the form of a large enough water source. This water source is named Sumber Nyolo, Sumber Nyolo is used by society for daily needs and it’s used for irrigating agricultural land, besides Ngenep Village there are four other villages from Singosari District that use it. In addition to use for daily needs and irrigation, currently the Sumber Nyolo area is starting to be developed into a tourist destination, tourism management is carried out by community groups who are members of the Sumber Nyolo Pokdarwis (Tourism Cognizant Group). The management pattern carried out by Pokdarwis is still relatively simple, besides that the quality varies. As a result of this, it affects the quality of natural resources and the cleanliness of the area. Based on the various explanations that have been explained, the problems in the Sumbernyolo area, Ngenep Village, Karangploso District, Malang Regency that urgently need a solution are as follows: (1) How to develop active participation of the surrounding community and Pokdarwis Sumbernyolo towards the development of educational tourism and conservation of the Sumbernyolo area? (2) How to prevent forest quality degradation? (3) How to utilize water resources through a wise use pattern? (4) How to organize and develop conservation areas and educational tourism in Sumbernyolo? The method of activities carried out is through an inventory of tourism potential, then a strategy for developing tourism destination areas (DTW) is carried out. For further socialization to the main tourism actors, namely Pokdarwis and the surrounding community who are involved about the direction of development of Sumbernyolo tourism. After the socialization, it was followed by improving tourism infrastructure and supporting elements such as empowering the surrounding community. The process will always be monitored and overall periodically. The results of the activities carried out consist of two aspects, namely the conservation of water sources and forests and the development of educational tourism facilities. The conclusion of this activity is that by carrying out this service activity, a direction for developing Sumber Nyolo tourism is formed towards conservation tourism and educational tourism areas.